"I haven't earned the right to just play around with my literacy programme": strategies, tactics and policy actors/subjects. Issue 2 (29th October 2021) - Tilson, Jane; Sandretto, Susan
Abstract : Purpose: The purpose of this New Zealand study is to analyse the influence of the literacy course from an initial teacher education degree, to support beginning teachers to view themselves as policy actors, not mere policy subjects. In our role as teacher educators, we sought to support beginning teachers to find freedom within the constraints of official literacy policy to include multiliteracies. Design/methodology/approach: Using de Certeau's dialectic of strategies and tactics, the authors critically analysed the influence of the literacy course. The data included an assignment from the literacy course, an end-of-literacy course survey and a follow-up interview six months into their first teaching position with a group of five beginning primary school teachers. Findings: The findings shed light on our apparent inability to support beginning teachers to see themselves as policy actors/subjects. The analysis reveals the beginning teachers' tactical responses to our strategies intended to position them as policy actors. The analysis also illustrates how the tactics the authors deployed were viewed as strategies by the beginning teachers, ironically further solidifying the literacy policy they had sought to critique and destabilise and (re)positioning them as policy subjects. Originality/value: de Certeau's framework supported the illumination of the complex interplay of strategies and tactics deployed by ourselves and beginning teachers as the authors sought to support them to identify the freedoms within the constraints of official literacy policy. Any future attempt to develop beginning teachers as policy actors/subjects will benefit from the careful examination of the strategies and tactics at play in initial teacher education.